2012
DOI: 10.4149/gpb_2012_025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood pro/antioxidant levels before and after acute exercise in athletes and non-athletes

Abstract: Abstract. The aims of our study were to assess the redox state of adolescent athletes and non-athletes both at rest and after acute exposure to physical load and to find relations between parameters of redox state and morphofunctional characteristics of subjects. 58 young handball players and 37 non-athletes were subjected to body composition analysis, measuring of maximal oxygen consumption and blood sampling immediately before and after a maximal progressive exercise test. At rest, athletes had significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…We also performed blood draws following the completion of the entire protocol, which might have affected the MDA-TBARS measurement. Because the blood draw was performed following the acute handgrip exercise and exercise can lead to acute increases in TBARS [10], it is possible that the lack of increase in TBARS could be due to the antioxidant supplement. However, conflicting studies demonstrated no change in TBARS following acute exercise [8,14] in age groups and intensities similar to that of our current study.…”
Section: Aa (N = 9)mentioning
confidence: 99%
“…We also performed blood draws following the completion of the entire protocol, which might have affected the MDA-TBARS measurement. Because the blood draw was performed following the acute handgrip exercise and exercise can lead to acute increases in TBARS [10], it is possible that the lack of increase in TBARS could be due to the antioxidant supplement. However, conflicting studies demonstrated no change in TBARS following acute exercise [8,14] in age groups and intensities similar to that of our current study.…”
Section: Aa (N = 9)mentioning
confidence: 99%
“…These findings are in line with previous studies, which states that regular exercise makes individuals stronger against oxidative stress, increases the activity of antioxidant defence system and reduces oxidant production. [17][18][19] Even though both athletes and non-athletes showed better results with moderate intensity exercise, athletes showed a dramatic improvement than non-athletes. Regular exercise also protects against diseases associated with chronic low-grade systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, further analysis showed that increased levels of H 2 O 2 and decreased SOD activity were observed only in a group of handball players with the lowest basal SOD activity [31]. Additionally, when comparing handball players with sedentary age-matched controls, exercise testing induced the increase in H 2 O 2 levels only in controls who had significantly lower basal SOD activity compared with handball players [4]. This suggests that adaptations of antioxidant defence due to chronic exercise protect athletes from oxidative stress induced not only by an exercise stimulus but also most likely in a number of non-exercise conditions.…”
Section: Statisticsmentioning
confidence: 99%
“…Although there are a few studies reporting the effects of treadmill exercise on redox state in football players or non-athletes [1,[33][34][35][36][37], the most adequate comparison of our results is with studies performed on young handball players [4,5,31], although the exercise test performed in these studies was cycling ergometer testing. However, because it has been shown that endogenous oestrogen may have a protective role in exercise-induced oxidative stress among female handball players [38] and female non-ath- exercise load and consequently longer duration of the exercise test.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation